Features of children’s leisure time in rear city during the Great Patriotic War (on the example of Omsk) - M. S. Nosova (Омский научный вестник: Серия "Общество. История. Современность")
The article uses the example of everyday life of Omsk children to study the main leisure practices during the Great Patriotic War. The study examines both personal sources and archival sources. The author examines the leisure time of children in the process of becoming a person. When devoting almost all the time to work, children still found the opportunity to communicate with their peers, develop and devote time to games